Short-chain fatty acids and ceca microbiota profiles in broilers and turkeys in response to diets supplemented with phytase at varying concentrations, with or without xylanase - González-Ortiz, G. (Poult Sci, 2020)
Two independent studies were performed, each with a 3 × 2 factorial arrangement to compare the response in broilers and turkeys to phytase and xylanase supplementation on cecal fermentation and microbial populations. For both studies, 960 Ross 308 and 960 BUT 10 (1-day-old) were allocated to 1 of 6 experimental treatments: (1) control diet, containing the standard dose (100 g/ton) of phytase (STD-Xyl); (2) the control diet with 100 g/ton of xylanase (STD + Xyl); (3) the control diet supplemented on top with 2 fold the standard dose of phytase (200 g/ton), also referred as superdosing (SD-Xyl); (4) the superdosed diet with 100 g/ton of xylanase (SD + Xyl); (5) the control diet supplemented with 5-fold the standard dose of phytase (500 g/ton), also referred as megadosing (MD-Xyl); and (6) the megadosed diet with 100 g/ton of xylanase (MD + Xyl). Each treatment had 8 replicates of 20 animals. Broiler and turkey diets, based on wheat, soybean meal, rapeseed, and barley, and water were available ad libitum. On day 28, the cecal contents from 5 birds per pen were collected. The profile of short-chain fatty acids (SCFA) and microbiome structure (by % guanidine and cytosine [G + C] method) were analyzed. Selected % G + C fractions were used for 16S rDNA sequencing for the identification of bacteria. No treatment effects were noted on SCFA concentrations in either broilers or turkeys. Broilers fed MD diets had greater proportions of unclassified Clostridiales, Mollicutes (RF9) and Faecalibacterium. Xylanase supplementation in broilers resulted in lower proportions of Lactobacillus but increased Mollicutes (RF9), unclassified Ruminococcus, unclassified Clostridiales, and Bifidobacterium. The microbiome in turkeys was unaffected by phytase supplementation, but xylanase supplementation increased the proportions of Lachnospiraceae (Incertae sedis), Lactobacillus, and Bifidobacterium. Supplementation of turkey diets with increasing doses of phytase did not affect the cecal microbiota in contrast to what was observed in broilers. In contrast, xylanase supplementation in both species led to significant changes in the microbial populations, suggesting a positive influence through the provision of oligosaccharides.